Contributes to the Profile of the Brazilian Literary Tourist: Experience and Motivation - Baleiro, Rita; Viegas, Margarida; Faria, Diomira (Anais Brasileiros de Estudos Turísticos, 2022)
This exploratory and quantitative research aims to contribute data on individuals engaging in literary tourism regarding organisation and preparation practices, visited literary places, travel motivations and surprising aspects of the experience. To collect data, an online questionnaire survey was sent to the participants in a literary festival, enquiring about previous literary-inspired visits. The findings indicate that writers’ house museums are the most visited literary tourist attraction and that visitors in an upper-income bracket prepare their literary-inspired visits autonomously by conducting online research and (re)reading the literary texts. In contrast, those in a lower-income bracket often rely on viewing audio-visual adaptations of books. Concerning the motivation to go on literary touring, most respondents indicate the amplification of knowledge about the literary work and the author. In the experience of literary tourism, the analysis of the data reveals there is an emotional and intellectual interaction in which imagination and visualisation intervene to co-create the literary place. These findings are analysed after the concepts of experience, motivation and de-differentiation in tourism studies and the concept of “realisation” borrowed from the transactional theory of meaning formation.